Different Modes of Transmission and Containment Strategies for COVID-19 - Khadka, Sitaram; Saeed, Hamid; Bajgain, Yogesh; Shahi, Janak; Yadav, Tank Prasad; Gupta, Ravi Prasad (Europasian Journal of Medical Sciences, 2020)
Coronavirus disease (COVID-19) is a respiratory infectious ailment caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The first outbreak of this disease occurred in China and declared a pandemic in a very short period of time. SARS-CoV-2 gets transmitted mainly through the respiratory tract by droplets or respiratory secretions and by direct contact with the infected person as well as indirect contact through touching the contaminated surface accompanied by poor hygiene practice. Until the vaccine, a therapeutic agent or any other treatment modality gets approved; contact tracing and management, social distancing, personal hygiene, respiratory etiquette, and environmental decontamination are the prime factors to be considered for transmission containment and hence for appropriate safety measures for COVID-19 which is possible with the support of social work from the community level.